Determinan Pendapatan Petani Alpukat di Dukuh Sodong Boyolali - Hakim, Muhammad Farid; Hidayah, Nur (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study, entitled "Determinants of Avocado Farmers’ Income in Dukuh Sodong, Boyolali," aims to analyze the influence of business capital, work experience, and selling price on farmers’ income, both partially and simultaneously. The research employs a quantitative method with a descriptive and causal approach, using primary data collected through questionnaires distributed to 59 avocado farmers in Dukuh Sodong, Boyolali. Data analysis was conducted through validity and reliability tests, multiple linear regression analysis, classical assumption tests, and hypothesis testing. The results indicate that the three independent variables simultaneously have a significant effect on income, contributing 56.4%. Partially, each variable (business capital, work experience, and selling price) has a positive and significant influence on farmers’ income.